Appraisal of the Roles of Metropole and Satellite in the Stunted Development of African Nation State Nigeria - Haruna, Ali; Ibrahim, Alhaji Ahmadu (Advances in Social Sciences Research Journal, 2016)
Issues relating to government in post -colonial states in Africa are replete with tales of woes when considered within the ambit of development, especially in this era of globalization. Many orthodox views hold the industrialized western nations of the north culpable. On the other hand, the nascent economic theorists of western origin implicate the fragile economic structures and institutions of governance and leadership as being responsible for Africa’s underdevelopment status. While the debate is on, some others view African status as endogenously inherent in her leadership response to the crises of poverty, food security political instability, technological development and other critical malaise. This paper explores the extent to which these views can be relevant explicate the failure of post-colonial states in Africa, with particular reference to Nigeria, in this discourse. The paper implicates the roles played by Nigerian comprador leadership, response to the call for economic political and cultural liberalization as the underlying factors responsible to the failure of the post-colonial Nigerian state.